HUBUNGAN TINGKAT KEPOSITIFAN BTA DENGAN PENINGKATAN JUMLAH NEUTROFIL (PROSENTASE) PADA PASIEN TB - Fiqi Fadhilah (FKU 15 UMY 585, 2015)

(untitled)
Background: Tuberculosis (TB) is one of the world's attention infectious disease today. Program Directly Observed Treatment Short course (DOTS) has been recommended byWHO as a strategy for detection and cure of TB patients, especially for new sputum smear-positive pulmonary TB case. Acid Fast Bacillus positivity level can act as a marker of the infectious degree whereas the hematological changes can act as a marker for the diagnosis, prognosis and response to therapy of TB disease. Researches reveal that neutrophils play some interesting roles; it can be called as a bi-directional weapon. Neutrophils are seen in the early stages of the mycobacterial infection. In chronic cases the same neutophils may act in the pathology of granuloma formation. Thus neutrophil act as a â€œDouble Edge Swordâ€. Neutrophils are found in 69% of the results of a complete blood count (neutrophils) in clinical patients with pulmonary tuberculosis. Methods: The research was performed by using observational analytic design with cross sectional approach. The sample of this research were 38TB patients aged 15-50 years old who has been done sputum examination and complete blood count at RS PKU Muhammadiyah Yogyakarta Unit 1. This study data analysis using Spearman correlation test method. Result: The prevalence TB in men was higher than women (74%: 26%). TB patients with AFB 1+ is 10 people (26%), AFB +2 is 13 people (34%) and the AFB +3 is 15 people (40%). The Spearman analysis result show that there is significantly relations between AFB positivity level and neutrophil count (p<0,05). TB patients with +1 AFB who has low neutrophil count is 1 people while has normal is1people. TB patients with 2+ AFB who has high neutrophils count is 12 people while has normal Hb levels is 5 person. TB Patients with 3+ AFB who has high neutrophil count is 8 people and normal neutrophil count is 5 person. Conclusions : TB patients with positive AFB sputum-smear mostly has high neutrophils. AFB sputum-smear positivity rate is associated with high neutrophils count in TB patients